The Role of Self-Awareness Training in Motivation For Hospital Workers - Shintya Putri Setiowati (Department of Psychology, Universitas Negeri Yogyakarta, 2020)
Hospital service improvement is associated with trusted personnel in treating patients. The form of supervision of Hospital accreditation is held every year. Hospital personnel requirements namely improving skills and updating knowledge related to the profession. But the problem faced by personnel is not being aware of their abilities. This is related to motivation or encouragement to personnel. The problem is seen, some personnel are less aware of the emotions they are feeling. Researchers conduct Self Awareness Training for hospital personnel. Participants numbered 18 personnel consisting of several sections in Hospital. Based on literature studies conducted by researchers, found a positive relationship between self-awareness and work motivation. Therefore, the researcher tried to implement a self-awareness training program to increase the work motivation of hospital personnel. The results of paired sample t-test analysis showed that there was a change in motivation after psychological capital training, with a significant value of 0,000 (p 0.05).